Fibroadipose vascular anomaly treated with sirolimus: Successful outcome in two patients. Issue 6 (16th November 2017) - Erickson, Jonathan; McAuliffe, William; Blennerhassett, Lewis; Halbert, Anne
Abstract: Fibroadipose vascular anomaly (FAVA) is a rare, complex mesenchymal malformation combining fibrofatty replacement of the affected muscles and slow‐flow vascular malformation. The condition is characterized by localized swelling, severe pain, phlebectasia, and contracture of the affected limb. Treatment paradigms are not well established for this rare, recently recognized condition. We report two cases of FAVA in which treatment with sirolimus produced rapid, dramatic improvement in pain and quality of life.